Severity Trajectories of Pediatric Inpatients Using the Criticality Index. - Rivera, Eduardo A. Trujillo (Pediatr Crit Care Med, 2021)
OBJECTIVES: To assess severity of illness trajectories described by the Criticality Index for survivors and deaths in five patient groups defined by the sequence of patient care in ICU and routine patient care locations. DESIGN: The Criticality Index developed using a calibrated, deep neural network, measures severity of illness using physiology, therapies and therapeutic intensity. Criticality Index values in sequential 6-hour time periods described severity trajectories. SETTING: Hospitals with pediatric inpatient and ICU care. PATIENTS: Pediatric patients never cared for in an ICU (n=20,091), patients only cared for in the ICU (n=2096) and patients cared for in both ICU and non-ICU care locations (n=17,023) from the 2009–2016 Health Facts® database (Cerner Corporation, Kansas City, MO). INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Criticality Index values were consistent with clinical experience. The median (25(th)-75(th) percentile) ICU Criticality Index values (0.878 (0.696, 0.966)) were more than 80-fold higher than the non-ICU values (0.010 (0.002, 0.099)). Non-ICU Criticality Index values for patients transferred to the ICU were 40-fold higher than those never transferred to the ICU (0.164 vs. 0.004). The median for ICU deaths was higher than ICU survivors (0.983 vs 0.875) (p<.001). The severity trajectories for the 5 groups met expectations based on clinical experience. Survivors had increasing Criticality Index values in non-ICU locations prior to ICU admission, decreasing Criticality Index values in the ICU, and decreasing Criticality Index values until hospital discharge. Deaths had higher Criticality Index values than survivors, steeper increases prior to the ICU, and worsening values in the ICU. Deaths had a variable course, especially those who died in non-ICU care locations, consistent with deaths associated with both active therapies and withdrawals/limitations of care. CONCLUSION AND RELEVANCE: Severity trajectories measured by the Criticality Index showed strong validity, reflecting the expected clinical course for 5 diverse patient groups.